Evaluation of maxillary bones using cone beam computed tomography: A systematic review - Pinheiro, Juliana; Morais da Silva, Luana Amorim; França, Glória Maria; de Melo Fernandes Almeida, Dennys Ramon; Feitoza da Silva, Amanda; Gomes da Silva, Gabriel (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
Cone beam computed tomography is widely used in dentistry, due to its easy accessibility, low cost and better accuracy compared to medical tomography. The present study aims to conduct a systematic review of the literature on the evaluation of jaw bones using cone beam computed tomography. A bibliographic search was performed in the electronic databases PubMed, Scopus, Embase and Web of Science. At the end of the analysis, 10 articles published between 1998 and 2015 were included. Cone beam computed tomography is a precise and fast method, used to evaluate digital images in high resolution, with sharpness, precision. In addition, the acquisition of these images is essential to measure bone elements, in quantity and quality. It should also be noted that the forecast of bone strength will depend on several factors, such as bone density and microarchitecture. Thus, the professional and reduces the likelihood of making mistakes, which interfere with the prognosis of dental treatment.